Determinants of Zinc Supplementation Utilization among Under-Five Children with Diarrhoea: A Systematic Review - Aprilya Roza Werdani; Fitria Mushollini; Icha Pranata Utami; Dini Nurmaita 'Aini; Rahayu Rika Destia; Hadijah Canmay; Ribby Gustiyanni (Fakultas Kedokteran, Universitas Papua, 2025)
Diarrhoea remains a major public health concern and a leading cause of morbidity and mortality among children, particularly in low- and middle-income countries. Although the World Health Organization recommends zinc supplementation as an adjunct therapy for childhood diarrhoea, its utilization remains suboptimal. This study systematically synthesized evidence on determinants of zinc supplementation utilization among children under five with diarrhoea. A systematic search was conducted in Taylor & Francis, ScienceDirect, and Google Scholar databases for studies published between 2020 and 2025, following PRISMA guidelines. Nine eligible studies were included, reporting zinc utilization prevalence ranging from 8.96% to 43.58%. Higher utilization was associated with maternal education, younger maternal age, media exposure, higher household income, smaller family size, health insurance coverage, prior awareness of zinc supplementation, and improved access to healthcare services. Lower utilization was observed among female children, rural residents, larger households, younger infants, and caregivers seeking initial treatment from non-formal sources. Strengthening caregiver education, improving healthcare access, and promoting zinc supplementation through primary healthcare systems are essential to improve childhood diarrhoea management.